2002
DOI: 10.1046/j.1471-4159.2003.01500.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient ischemia enhances tyrosine phosphorylation and binding of the NMDA receptor to the Src homology 2 domain of phosphatidylinositol 3‐kinase in the rat hippocampus

Abstract: Tyrosine phosphorylation of the NMDA receptor has been implicated in the regulation of the receptor channel. We investigated the effects of transient (15 min) global ischemia on tyrosine phosphorylation of NMDA receptor subunits NR2A and NR2B, and the interaction of NR2 subunits with the SH2 domain of phosphatidylinositol 3-kinase (PI3-kinase) in vulnerable CA1 and resistant CA3/dentate gyrus of the hippocampus. Transient ischemia induced a marked increase in the tyrosine phosphorylation of NR2A in both region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 52 publications
3
42
0
Order By: Relevance
“…Among tyrosine residues on GluN2 subunits, Tyr1336, located in the intracellular C-terminal domain of GluN2B, is phosphorylated and may bind to the SH2 domain of the p85 subunit of PI3-kinase. Tyrosine phosphorylation of GluN2B is enhanced, and the binding of tyrosine phosphorylated GluN2B subunits to the SH2 domain of PI3-kinase is increased, after cerebral ischemia (15,16). Interestingly, the SH2 domain of PI3-kinase does not bind to the GluN2A subunit after cerebral ischemia, although a larger increase in the tyrosine phosphorylation of GluN2A than in that of GluN2B is observed.…”
Section: Tyrosine Phosphorylation Of Glutamate Receptors In the Ischementioning
confidence: 97%
“…Among tyrosine residues on GluN2 subunits, Tyr1336, located in the intracellular C-terminal domain of GluN2B, is phosphorylated and may bind to the SH2 domain of the p85 subunit of PI3-kinase. Tyrosine phosphorylation of GluN2B is enhanced, and the binding of tyrosine phosphorylated GluN2B subunits to the SH2 domain of PI3-kinase is increased, after cerebral ischemia (15,16). Interestingly, the SH2 domain of PI3-kinase does not bind to the GluN2A subunit after cerebral ischemia, although a larger increase in the tyrosine phosphorylation of GluN2A than in that of GluN2B is observed.…”
Section: Tyrosine Phosphorylation Of Glutamate Receptors In the Ischementioning
confidence: 97%
“…In this sense, it is interesting that transient global ischemia induced a rapid and sustained increase in the tyrosine phosphorylation of NR2 subunits in the hippocampus. 18,29) In addition to the possible effects of mGluR5-mediated increases in tyrosine phosphorylation of NR2A and NR2B on NMDA receptor ion channel properties, tyrosine phosphorylation may also modulate calpain-mediated truncation of receptor subunits. Src-mediated tyrosine phosphorylation significantly reduced calpain-induced truncation of NR2A and NR2B.…”
Section: Discussionmentioning
confidence: 99%
“…30) It has also been shown that tyrosine phosphorylated NR2B, but not NR2A, can bind to the SH2 domain of PI3-kinase. 29,31) In transfected HEK293 cells, the tyrosine dephosphorylation of Tyr-842 in NR2A induced downregulation of recombinant NR1/NR2A receptor. 32) Therefore, it is conceivable that a sustained increase in the tyrosine phosphorylation of NR2A subunit could not induce a sufficient downregulation of the NMDA receptor, although tyrosine phosphorylation sites in NR2A and NR2B mediated by mGluR5 in hippocampal neurons remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental protocol was approved by the Committee of Animal Care and Use of Tokyo University of Pharmacy and Life Science. Transient (15 mins) forebrain ischemia was produced by the four-vessel occlusion procedure for rats described previously (Takagi et al, 2003). In brief, rats were anesthetized intraperitoneally with 40 mg/kg sodium pentobarbital.…”
Section: Animal Modelmentioning
confidence: 99%